The Relationship between Knowledge and Perceptions with the Completeness of the COVID-19 Vaccination for Students in Yogyakarta - Latifahanun, Este; Mahardika Ratih Resti Andani (Sahabat Publikasi Kuu, 2024)
Coronavirus 2019 (COVID-19) is a disease caused by a new type of acute respiratory syndrome (SARSCOV-2) strain. The virus is transmitted through droplets that are spread when coughing, sneezing, and talking. in Indonesian there was an increase in confirmed cases of COVID-19, which was previously 10-20 cases per week, increasing to 267 cases per week in the period 28 November- 2 December 2023. The government’s COVID-19 immunization campaign is one of its most successful attempts to interrupt the chain of transmission. The research aims to determine the relationship between the knowledge and perceptions of students pursuing higher education in Yogyakarta with the completeness of the vaccines they receive. The research uses an analytical design through a cross-sectional approach. The population is all students who are studying at Yogyakarta universities. The sample obtained was 107 students, the sampling technique uses consecutive sampling. Bivariate analysis used the Chi-Square test. The research results showed a significant relationship between knowledge and completeness of vaccination (p value = 0.002) and perception and completeness of vaccination (p value = 0.014). Better educational efforts from professionals are needed so that students understand more about the COVID-19 disease and the vaccine, because the majority of student respondents already understand it and have a positive perception. This will increase awareness and willingness to get the full vaccine. Keywords : COVID-19 vaccine, knowledges, perseptions